The perception of pregnant women about humanized childbirth and obstetric violence: experience report (Research, Society and Development, 2020)
This work aims to report the perception of pregnant women regarding humanized childbirth and obstetric violence and identify which practices pregnant women associate with humanized childbirth and obstetric violence. This is an experience report based on the problematization methodology approached together in the Charlez Maguerez arc. The arc is composed of five stages: observation of reality, survey of key points, theorization, hypotheses of solution and return to reality. Before that, it was found a significant number of pregnant women who suffered from practices that constitute obstetric violence, but not associated with them, said as a negligence in care during the delivery process, pointing to the quality of care provided, highlighting the lack of knowledge of pregnant women about their rights and the theme of humanized childbirth. It is concluded that much progress has been made in the search for humanization, however, there are still distortions about the humanization process, emphasizing that women need to be instructed in prenatal care, giving them incentives to be protagonists of their lives, including not only reproductive life, but also their empowerment, to defend themselves any form of violence.